Efficiency improvement of vehicles using temperature controlled exhaust thermoelectric generators. (1st January 2020) - Brito, F.P.; Pacheco, N.; Vieira, R.; Martins, J.; Martins, L.; Teixeira, J.; Goncalves, L.M.; Oliveira, J.; Hall, M.J.
Graphical abstract: Highlights: Control of thermoelectric module hot side temperature was achieved in driving cycles. Use of thermosiphon between heat source and application allowed temperature control. It was possible to model a variable conductance thermosiphon under variable pressure. Top thermoelectric efficiency is due to high heat usage, optimal hot face temperature. 6% fuel economy/CO2 reduction, breakthrough output obtained for light duty car. Abstract: One of the main obstacles for the use of thermoelectric generators (TEGs) in vehicles is the highly variable thermal loads typical of driving cycles. Under these conditions it will be virtually impossible for a conventional heat exchanger to avoid both thermal dilution under low thermal loads and TEG overheating under high thermal loads. The authors have been exploring an original heat exchanger concept able to address the aforementioned problems. It uses a variable conductance thermosiphon-based phase-change buffer between the heat source and the TEGs so that a nearly constant, optimized temperature is obtained regardless of operating conditions. To the best of the authors' knowledge, the thermal control feature of the system is unique among existing TEG concepts. The novelty of the present work is the actual computation of operating pressure and temperature and the corresponding vaporization and condensation rates inside the thermosiphon system during driving cycles along with the assessment of the influence of the volumes and pre-charge pressure on electrical output. The global energy and emission savings were also computed for a typical yearly driving profile. It was observed that indeed the concept has unparalleled potential for improving the efficiency of vehicles using TEGs, with around 6% fuel and CO2 emissions savings using the system. This seems a breakthrough for such light duty applications since the efficiency of conventional (passive) systems is strongly deprecated by thermal dilution under low thermal loads and the need to by-pass high thermal load events to avoid overheating. On the contrary, the present concept allows the control of the hot face temperature of the TEGs even under highly variable thermal load (i.e. driving cycle) environments.